Using Animated Video to Teach Narrative Text: A Case Study in an Indonesian Secondary School - Kartadiwangsa, R. Indra Kusuma; Arianti, Dwi; Jati, Sigit Pramono (ICONELT, 2024)
Recently, there has been an increase in the use of multimedia resources in learning methods to bring more understanding and curiosity to the students. From the many forms of multimedia, videos in the form of animations are attractive because the narratives and visuals developed in them are dynamic. These enable the learners to easily study and make the complicated texts of narrative material more interesting. The current research at SMAN 15 Surabaya was carried out with 11th-grade students and aimed to find out the advantages, disadvantages, and effectiveness of teaching using animated videos when teaching narrative texts. Data collection in the research was implemented in the form of a qualitative approach. The interviewer had taken observations from the teacher with the help of interviews in structural form, which included an in-depth discussion of experiences, strategies, and observations performed by the teacher. Meanwhile, the feedback from the 11th-grade students of SMAN 15 Surabaya was given using Google Forms, which had qualitative questions in order to obtain their level of engagement and comprehension of narrative texts, as well as personal preferences. The approach gives a clear insight into the perceptions and practical use of animated video as an instructional tool.